IMPLEMENTASI KEBIJAKAN BANTUAN LANGSUNG BENIH UNGGUL SEKOLAH LAPANG-PENGELOLAAN TANAMAN TERPADU (BLBU SL-PTT) PADI TAHUN 2012 DI KABUPATEN BARITO UTARA - , PARYANTO, Dr. Agus Pramusinto, MDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study analyzed a problem on implementation of program policy of Bantuan Langsung Benih Unggul Sekolah Lapangan Pengelolaan-Tanaman Terpadu /BLBU SL-PTT (Excellent Seed Direct Aid for Field School of Integrated Plant-Management) of rice in 2012 in North Barito Regency. The focus of the study would observed the lowness of adoption level of excellent seed usage amongst BLBU recipient small farmer (peasant). The study was done in South Teweh Subdistrict, North Barito Regency. South Teweh Subdistrict was chosen as a study location because in this area there is both semi technical irrigated land and rainfall receptacle land, and the area was rice producer center. There are 3 (three) villages in South Teweh Subdistrict, those are